2021
DOI: 10.2196/24947
|View full text |Cite
|
Sign up to set email alerts
|

Association of Smartphone Ownership and Internet Use With Markers of Health Literacy and Access: Cross-sectional Survey Study of Perspectives From Project PLACE (Population Level Approaches to Cancer Elimination)

Abstract: Background Telehealth is an increasingly important component of health care delivery in response to the COVID-19 pandemic. However, well-documented disparities persist in the use of digital technologies. Objective This study aims to describe smartphone and internet use within a diverse sample, to assess the association of smartphone and internet use with markers of health literacy and health access, and to identify the mediating factors in these relatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 54 publications
(62 reference statements)
4
20
0
Order By: Relevance
“…The current study has been able to determine/compare how widely internet accessibility and affordability affect health literacy outcomes among the different regions with different socioeconomic statuses. Our findings are consistent with others, showing that improved accessibility to the internet is able to provide better health education (40), particularly during the current COVID-19 environment with significant curtailment of face-to-face education opportunities (41).…”
Section: Discussionsupporting
confidence: 92%
“…The current study has been able to determine/compare how widely internet accessibility and affordability affect health literacy outcomes among the different regions with different socioeconomic statuses. Our findings are consistent with others, showing that improved accessibility to the internet is able to provide better health education (40), particularly during the current COVID-19 environment with significant curtailment of face-to-face education opportunities (41).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we simultaneously examined site, provider, and patient characteristics associated with telehealth and video use in PC and confirmed that racial/ethnic minority groups were more likely to use telephone than video, consistent with both VA and non-VA research [ 1 , 6 , 41 , 47 ]. Although studies on inequities regarding access to virtual care are inconsistent [ 48 50 ], major gaps persist in access to cellular data, video-capability, computer devices, adequate/high speed internet coverage and connectivity, which cannot be ignored when examining utilization of virtual care for all patient populations [ 13 ]. One component of addressing the racial/ethnic variations involves tackling the digital divide [ 51 ], as select groups, such as older individuals, and those living in rural areas, as well as individuals with socioeconomically disadvantaged backgrounds, may have more limited access to the internet or camera-enabled devices [ 51 – 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is vital that these recordings are reviewed by a neurologist with expertise treating patients with epilepsy to differentiate epileptic seizures from FS based upon video recording alone. This has limitations for medical professionals who lack epilepsy training [3] , [24] and for non-neurologists [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Smartphones are ubiquitous [5] , [23] , easy to use, and are available immediately for recording any events that may arise at a given time. One study of a diverse population in the US showed 96% of people surveyed had access to a mobile phone and 83% own a smartphone [24] . On the other hand, there are only 230 accredited specialized epilepsy centers in the US where patients can be admitted and monitored using video-EEG [25] .…”
Section: Introductionmentioning
confidence: 99%